Who was Kobe Bryant? - Labrecque, Ellen; Copeland, Gregory (New York : Penguin Workshop, 2020)
An illustrated biography of professional basketball player Kobe Bryant.
Includes bibliographical references (pages 48-49).
5.7
3-6
910L
W
Keywords: Bryant, Kobe, -- 1978-2020 -- Juvenile literature; Basketball players -- United States -- Biography -- Juvenile literature; Bryant, Kobe, -- 1978-2020.; Basketball players; African Americans -- Biography; Biographies